Measuring Technical Efficiency of Pepole's Bank of Srilanka - Selvamalai, T.; Uthayakumar, S.S. (South Eastern University of Srilanka, 2016)
The study measures the technical efficiency of People’s Bank from 2001 to 2015 by using Data Envelopment Analysis (DEA). The data was gathered from various Annual Reports of People’s Bank. The study mainly used input oriented CCR and BCC model of DEA. The study selected one output variable (Net profit) and four inputs variables (No. Of employees, investment, loans and advance, and liabilities). The study found that the average overall technical, pure technical and scale inefficiency of People’s Bank were 27.9%, 4.7%, and 23.8% respectively during the study period, there were full efficiency in 2011 and 2015 and there were technical inefficiency in other years. Further, technical efficiency score of People’s Bank in SriLanka had been improved.
Keywords: People's bank; Data Envelopment Analysis; Technical Efficiency